Implikasi Pengujian Ketetapan MPR dalam Sistem Ketatanegaraan Republik Indonesia Pasca Putusan Mahkamah Konstitusi No. 75/PUU-XII/2014 - Tomi Agustian (Lex Renaissance, 2016)
AbstractThis research studies the problems about: first, the base of Constitutional Court (MK) does not accept any application of judicial review of MPR (provisional people’s consultative assembly), second, the implication of the trial of MPR provisions in post-verdict of Constitutional Court. This research is a normative research that obtained primary legal materials in the form of the Verdict of Constitutional Court and supported with books, articles and documents. The results of the research concluded that first; the Constitutional Court in accordance with the Constitution 1945 Article 24C Sentence (1) does not have any authority to test the provision of MPRS. Second, the implication of the verdict of Constitutional Court does not cause the absence of mechanism of the trial of the MPR’s provisions; thus causing the legal vacuum and the absence of the institution that is authorized to do a trial towards the MPR’s provisions (tetraa incognita).   Keywords: Implication, trial, provision of MPR, verdict of constitutional court